Influence of Sulfate, Phosphate, Ammonia and Dissolved Oxygen on Biochemical Oxygen Demand of Marlimund Lake, Ooty, The Nilgiris: Influence of Sulfate, Phosphate, Ammonia and Dissolved Oxygen on Biochemical Oxygen Demand of Marlimund Lake, Ooty, The Nilgiris - Devapriya, J. Prescilla (International Journal of Pharmaceutical & Biological Archive, 2018)
The present study was done to ascertain the level biochemical oxygen demand (BOD) of Marlimund Lake situated in Ooty how it is related with the other parameters such as water temperature, dissolved oxygen, phosphate, sulfate, iron, and free ammonia. Four sampling sites were selected and studied over the period of 13 months from February 2016 to February 2017. The results were computed by best model fits applied for calculation using Curve Expert Version 4.2. The water temperature ranged from 8.1°C to 18.7°C, dissolved oxygen 3.468–6.976 mg/l, phosphate 0.1–1.92 mg/l, sulfate 1–18 mg/l, free ammonia 0.12–6.01 mg/l, and BOD 2.178–5.040 mg/l. BOD was found to be significantly related to dissolved oxygen (r = 0.5690291) by 4th degree polynomial fit, phosphate (r = 0.7095253) by rational function fit and free ammonia (r = 0.7395016) by MMF model fit, respectively. Sulfate was found to be nonsignificant (r = 0.2565396) by geometric fit model, and water temperature (r =0.4595060) shows a sinusoidal fit.